Efficacy and safety of Jianpi Qinghua granules for non-erosive reflux disease with spleen deficiency and damp-heat syndrome: a multicenter, randomized, double-blind, placebo-controlled clinical trial - Tai Zhang; Tai Zhang; Tai Zhang; Tai Zhang; Guang Bai; Wei Wang; Lin Liu; Zhenghua Zhou; Haijie Ji; Beihua Zhang; Beihua Zhang; Beihua Zhang; et al. (Frontiers in Nutrition)
BackgroundNon-erosive reflux disease (NERD), the most frequent phenotype of gastroesophageal reflux disease, presents without visible esophageal mucosal damage but significantly impacts patients' quality of life. Current treatments like proton pump inhibitors show limited efficacy for many NERD patients, necessitating alternative approaches. Jianpi Qinghua (JQ) granules, a traditional Chinese medicine, have shown promise in treating NERD by targeting symptoms of spleen deficiency and damp-heat syndrome.PurposeThis study aims to evaluate the efficacy and safety of JQ granules in treating patients with NERD characterized by spleen deficiency and damp-heat syndrome.Study designA multicenter, randomized, double-blind, placebo-controlled clinical trial was conducted with a total of 78 NERD patients randomly assigned to receive either JQ granules or placebo for 4 weeks, followed by a 4-week follow-up period.MethodsSeventy-eight NERD patients with spleen deficiency and damp-heat syndrome were recruited and randomly assigned to receive either JQ granules (n = 39) or placebo (n = 39). The trial included a 1-week lead-in, followed by a 4-week double-blind treatment, and a 4-week follow-up. Primary endpoints were the improvement rates of reflux and heartburn symptoms and VAS score changes. Secondary endpoints included atypical symptom scores, total TCM syndrome scores, GERD Health-Related Quality-of-Life (HRQL), and self-rated depression and anxiety scales. Safety assessments involved routine blood, urine, and liver and kidney function tests.ResultsAfter 4 weeks, the improvement rate for reflux or heartburn symptoms was 79.49% in the JQ group vs. 58.97% in the placebo group (P < 0.05). VAS scores showed significant reductions in both groups but without notable inter-group differences. Total TCM syndrome scores significantly decreased in both groups, with the JQ group showing greater improvement trends. The JQ group had higher rates of effective TCM syndrome improvement and better GERD-HRQL scores. Both groups saw significant reductions in self-rated depression and anxiety scores, with trends favoring JQ granules. Safety assessments were comparable between groups.ConclusionJQ granules significantly outperform placebo in treating NERD symptoms and display long-term effectiveness. They effectively address spleen deficiency and damp-heat syndrome, improving patients' social functioning, and have a favorable safety profile.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT04324138?term=NCT04324138&rank=1, identifier: NCT04324138.